SISTEM PEMBUANGAN SAMPAH OTOMATIS MENGGUNAKAN AUTOMATIC GUIDED VEHICLE BERBASIS GPS ULTRASONIK - Yonanta, Rhesty Dian; Maslan, Andi (LPPM Universitas Putera Batam, 2020)
ABSTRACT In a housing complex, there are many conditions that make people do not care about cleanliness in the environment because there are various factors that are mostly caused by the waste disposal site is too far away and the time of collection of garbage for TPS officers when taking garbage to housing is not timely and less disciplined due to limitations labor so that a solution will be needed to overcome these problems. In this final project an automatic waste disposal system will be designed using an ultrasonic GPS-based automatic guide vehicle. In the robot car will be programmed a timing that will set the time lag needed for this robot car to take garbage from one house to another following the route that has been set. The way this robot works if there is a blockage in front of the house automatically it will automatically stop and because there is an Ultrasonic GPS sensor that helps it. The results of the final project of an automatic garbage disposal system using an ultrasonic GPS-based automatic guide vehicle can transport as much as 5kg of garbage. To run this robot using the Arduino Uno. Keywords: Rubbish, Automatic guide vehicle, GPS ultrasonik